Environmental dan Sustainability: Dampak Terhadap Kinerja Perusahaan - Andrik Gastri Widjatmiko; Sari, Airlin Permata (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study examines and identifies the impact of Sustainability Performance and ISO 14001 on the Company Performance of infrastructure sector companies listed on the IDX. Data is collected from the company's annual report and sustainability report. Approach A quantitative approach is used to collect relevant data from the entire population of 63 companies listed on the Indonesia Stock Exchange. After purposive sampling, 56 listed companies were finally considered. The authors measured Company Performance using Tobin's Q. After collecting the data, the authors analyzed it with multiple linear regression and MRA. The findings reveal the significant negative impact of Sustainability Performance and ISO 14001 on Company Performance. Furthermore, the variable Corporate Governance is proven not to moderate between Sustainability Performance and ISO 14001 on Company Performance